Resistance to chloroquine by Plasmodium vivax in Irian Jaya, Indonesia. - Baird, J; Basri, H; Purnomo; Bangs, M; Subianto, B; Patchen, L; Hoffman, S (1991)
Evidence of emerging resistance to chloroquine by Plasmodium vivax is described from Irian Jaya (Indonesian New Guinea). Sixteen of 24 residents in the village of Arso PIR II taking supervised weekly chloroquine prophylaxis (5 mg base/kg) had asexual parasitemia with P. vivax at least once during eight weeks of surveillance. An American working in the same village developed symptomatic P. vivax parasitemia despite chloroquine prophylaxis. Five days after therapy with 600 mg chloroquine base, the asexual parasitemia in the American increased 40-fold, but cleared after treatment with 1,500 mg chloroquine base. Serum samples were not available from many of the cases, but six local residents and the American had serum levels of chloroquine in excess of the ordinarily suppressive 15 ng/ml at the time of their asexual parasitemias (16-70 ng/ml). The weekly 300 mg base tablet of chloroquine, which has been the standard for prophylaxis against malaria for more than 40 years, was not effective against P. vivax in Arso PIR, Irian Jaya.